Occurrence and characterization of Shiga toxin-producing Escherichia coli (STEC) isolated from Chinese beef processing plants. (October 2020) - Dong, Pengcheng; Xiao, Tongtong; Nychas, George-John E.; Zhang, Yimin; Zhu, Lixian; Luo, Xin
Abstract: In order to investigate the prevalence, O serogroup, virulence genes and antibiotic resistance of Shiga toxin-producing Escherichia coli (STEC) in two beef plants in China, a total of 600 samples collected from 6 sites (feces, hide, pre-evisceration carcasses, post-washing carcasses, chilled carcasses and meat, 50 samples per site in each plant) were screened for the existence of Shiga toxin-encoding genes by PCR. STEC strains in positives were isolated and characterized for serogroup and antibiotic sensitivity. The PCR prevalence rate in each site was 45.0%, 31.0%, 14.0%, 13.0%, 9.0% and 18.0%, respectively. Sixteen O serogroups including O157, O146 and O76 which are associated with disease were identified. The existence of both stx 1 and stx 2 genes was the most common among the isolated strains (42.3%). Among the overall 26 isolates, seven and three were resistant to at least three and ten antibiotics, indicating a high antibiotic resistance in STEC strains isolated from the study.